Nitrogen fertilization form and energetic status as target points conditioning rice responsiveness to elevated [CO2] - Jauregui, Ivan; Mitsui, Toshiaki; Gakière, Bertrand; Mauve, Caroline; Gilard, Françoise; Aranjuelo, Iker; Baslam, Marouane (Frontiers in Plant Science, 2025)
The nitrogen (N) fertilization form and plant energy status are known to significantly influence plant responses to elevated atmospheric carbon dioxide (CO2) concentrations. However, a close examination of the interplay between N sources under contrasting light intensity has been notably absent in the literature. In this study, we conducted a factorial experiment with rice plants involving two different light intensities (150 and 300 µmol m-2 s-1), inorganic N sources [nitrate (N-NO3) or ammonium nitrate (N-NH4NO3)] at varying CO2 levels (410 and 700 parts per million, ppm). The aim was to examine the individual and combined effects of these factors on the allocation of biomass in whole plants, as well as on leaf-level photosynthetic characteristics, chloroplast morphology and development, ATP content, ionomics, metabolomics, and hormone profiles. Our research hypothesis posits that mixed nutrition enhances plant responsiveness to elevated CO2 (eCO2) at both light levels compared to sole N-NO3 nutrition, due to its diminished energy demands for plant assimilation. Our findings indicate that N-NO3 nutrition does not promote the growth of rice, its photosynthetic capacity, or N content when exposed to ambient CO2 (aCO2), and is significantly reduced in low light (LL) conditions. Rice plants with N-NH4NO3 exhibited a higher carboxylation capacity, which resulted in larger biomass (total C, tiller number, and lower root-shoot ratio) supported by higher Calvin-cycle-related sugars. The lower leaf N content and overall amino acid levels at eCO2, particularly pronounced in N-NO3, combined with the lower ATP content (lowest at LL and N-NO3), may reflect the higher energy costs of N assimilation at eCO2. We also observed significant plasticity patterns in leaves under eCO2. Our findings highlight the importance of a thorough physiological understanding to inform innovative management practices aimed at mitigating the negative effects of climate change on plant N use efficiency.